AKIBAT HUKUM BERAKHIRNYA HAK MILIK ATAS TANAH TERHADAP KREDITUR PEMEGANG HAK TANGGUNGAN - SANIAH, SANIAH (LP2MTBM MAKARIOZ, 2024)
This article discusses the legal consequences that occur with the the expiration of land property rights against creditors holding mortgage rights. Land property rights can be used as debt collateral encumbered by mortgage rights and property rights can end due to various reasons. Mortgage rights, which are material security over land, are intended to guarantee the ayment of debtors’ debts. However, when the title to the land is removed, it has a significant impact on the creditor of the holder of the mortgage right because it loses the priority right to be able to execute the collateral object as a source of collecting receivables, the creditor of the holder of the mortgage right who is in the position of a preference creditor whose debt is guaranteed paymemt from the collateral object changes its its position to a concurrent creditor.